Perspektif Masyarakat dalam Penerapan Digitalisasi Pertanian - Hari Yati Nur; Yoshua Putrawan Simanjuntak; Kayla Devina Azzahra; Jonathan Sitohang; Zefania Intan Kusuma; Melia Ari Santi; Elsa Ramadhan; Agief Julio Pratama; M. Iqbal Nurulhaq; Tri Budiarto; Widya Hasian Situmeang; Ratih Kemala Dewi; Restu Puji Mumpuni; Edi Wiraguna (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
This study aims to determine the perspective of the Ciherang Village community on the implementation of agricultural digitalization. As the digital era develops, the use of technology in agriculture is a great opportunity to increase efficiency and production results. Through a qualitative approach, data were obtained from questionnaires with farmers and local community leaders. The results of the study showed that most people are interested in the use of agricultural digitalization, especially in terms of access to fertilizer information and marketing of crops. However, its implementation still faces obstacles such as low digital literacy, limited technological devices, and minimal digital understanding. Therefore, mentoring efforts, ongoing training, and improving digital infrastructure are needed so that agricultural digitalization can be implemented effectively and provide real benefits for farmers in Ciherang Village.